(untitled) (Research, Society and Development, 2021)
Araucaria angustifolia var. angustifolia and Araucaria angustifolia var. indehiscens, seeds (common pinhão and monkey pinhão) are consumed after cooking, coats and water represent waste. In this work, pinhão was submitted to different cooking conditions, the water extracts were analyzed to determine and identify their phenolic compounds content, antioxidant activity and antimicrobial potential. Cooking for 45 minutes without addition of sodium chloride resulted in residual water with highest content of phenolic compounds and antioxidant activity (DPPH and FRAP), both for the common pinhão and for the monkey pinhão. Protocatecuic acid, vanillin and coniferaldehyde were identified and quantified by HPLC-ESI-MS/MS as the most prevalent phenolic compounds. No antimicrobial potential was observed against Salmonella enterica Typhimurium (ATCC 14028), Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923) and Bacillus cereus (ATCC 11778).